(untitled) (Research, Society and Development, 2022)
Cell phones are an important social tool in everyday life, as they facilitate communication processes and allow people to approach quickly and efficiently. Its indiscriminate use in clinical environments by health professionals can contribute to the phenomenon of bacterial resistance, since it serves as a carrier of several microorganisms, and among them they can contain some with high pathogenicity and that present intrinsic virulence mechanisms, such as formation of Biofilms. Therefore, the objective of the present study was to analyze the profile of bacterial isolates from cell phones of health professionals from different sectors in a hospital of Recife, Pernambuco-Brazil, taking into account their resistance profile and their virulence factor, such as biofilm formation. Microbiological data from 10 isolates from cellular devices of health professionals were investigated. The isolates were seeded in specific culture media and the potential for biofilm formation was evaluated on Congo red agar and the isolates were characterized for their antimicrobial resistance profile. As a result, a profile of contamination of cell phones by resistant microorganisms and biofilm producers was obtained, as well as alarming data on the spread of bacterial resistance. In view of the results found, it is concluded that cell phones are important sources of propagation of bacterial resistance, requiring better hygiene processes for their use in the clinical and therapeutic environment, so that they do not put patients in hospital beds at risk. ICU’s.